2015
DOI: 10.1073/pnas.1513012112
|View full text |Cite
|
Sign up to set email alerts
|

Nanopurification of silicon from 84% to 99.999% purity with a simple and scalable process

Abstract: Silicon, with its great abundance and mature infrastructure, is a foundational material for a range of applications, such as electronics, sensors, solar cells, batteries, and thermoelectrics. These applications rely on the purification of Si to different levels. Recently, it has been shown that nanosized silicon can offer additional advantages, such as enhanced mechanical properties, significant absorption enhancement, and reduced thermal conductivity. However, current processes to produce and purify Si are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 37 publications
1
45
0
3
Order By: Relevance
“…Traditionally, silicon nanostructures are fabricated either from top-down (chemical etching) or bottom-up (CVD) method, which typically involve either toxic silane precursors or expensive high purity silicon sources. Recently, it is found that various low grade silicon [7,48,88,89,90] and natural sources [91][92][93][94][95][96] can serve as cost-effective sources to produce nanostructured silicon for lithium-ion battery.…”
Section: Low Raw Materials Costmentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, silicon nanostructures are fabricated either from top-down (chemical etching) or bottom-up (CVD) method, which typically involve either toxic silane precursors or expensive high purity silicon sources. Recently, it is found that various low grade silicon [7,48,88,89,90] and natural sources [91][92][93][94][95][96] can serve as cost-effective sources to produce nanostructured silicon for lithium-ion battery.…”
Section: Low Raw Materials Costmentioning
confidence: 99%
“…The purity of these obtained nanoparticles can also be improved by acid etching processes up to 99.999% (wt%). [7] During high energy ball-milling processes, the impurity-rich regions containing Fe, Al, and Ca are mechanically weak, can be easily exposed on the surface, and be effectively removed through acid etching. Therefore, it can be easily understood that the purity goes up with the smaller size of Si particles in this nanopurification process (Figure 11b).…”
Section: Low Grade Siliconmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are also some other analytical methodologies, such as Atomic absorption spectrometry with graphite furnace (AASGF) with the limit of detection limit range between 10 -400 ppb [20], Spark source mass spectrometry (SSMS) with detection limit of sub ppm [60], X-ray fluorescence (XRF) with detection limit of 0.001% [61], and van der Pauw Hall effect measurement [18] [62]. The detailed comparison of these high purity analysis methods has been presented in Table 4.…”
Section: Trometry (Icp-ms/icp-oes)mentioning
confidence: 99%
“…In support of the scientific and technological feasibility of the proposed charge qubit, the purity of silicon in modern high-volume commercial nanometer-scale CMOS has dramatically increased since the previous wave of realizations of the charge qubit [39]. This has been driven by increasingly sophisticated CMOS lithographic processes with ultrahigh switching speed of devices as well as improved defect tolerances, required to achieve ever increasing densities of functioning transistors (tens of millions per mm 2 ) on microprocessor chips.…”
Section: Introductionmentioning
confidence: 99%